The Effect of PDDIKTI System Acceptance, Social Influence and Technology on Performance Expectations at Jember State Polytechnic Through Educational Background as an Intervening Variable - Yuvianti, Ike Agustin; Nursaid; Santoso, Budi (Ilomata International Journal of Management, 2026)
This study aims to analyze the influence of PDDIKTI system acceptance, social influence, and technology quality on the performance expectations of academic operators at the Jember State Polytechnic. This research is a type of comparative causal research. The data used in this study are primary data. The population in this study is the operator of the Jember State Polytechnic PDDikti management of 100. The sample was determined to be 100 respondents. The analysis model used in this study is Structural Equation Modeling (SEM) analysis with the help of WarpPLS software. The results of the study show that the acceptance of the PDDikti system, social influence, and technology have a positive and significant effect on the performance expectations of academic operators. The study offers practical value for higher education institutions looking to improve system performance expectations through training and social support. However, a clearer articulation of how these recommendations translate into measurable policies would increase social relevance.